205 An Adjusted SID-Thr:Lys Ratio Offsets Growth Performance Depressions in Finishing Pigs Fed Moderately High Distillers Dried Grains with Solubles (DDGS). (30th November 2020) - Norton, Sharon A; Xue, Pengcheng; Ramer, Brian; Erickson, Jim
Abstract: Two experiments were conducted to determine the impact of dietary SID Thr:Lys ratio (THR) on the performance of grow-finishing pigs. In Experiment 1, a total of 1, 152 pigs (initial BW = 21.0 ± 1.4 kg; 12 pens/treatment; 24 pigs/pen) were used in a randomized complete blocked design, with a 2 x 2 factorial arrangement of treatments containing 2 levels of DDGS (0 vs 25%) and 2 levels of THR (Low vs. High, 0.60 vs 0.67). Equal energy and nutrient levels that met or exceeded NRC (2012) requirements were achieved across treatments. A total of 1, 056 pigs (initial BW=18.6 ± 1.9 kg; 16 pens/treatment; 22 pig/pen) were used in Experiment 2 with the same experimental design, except for the SID Thr:Lys ratios were formulated to 0.60, 0.60, 0.61, 0.62 and 0.63 in 5 dietary phases for Low THR, and +0.03 for all phases in High THR. The MIXED procedures were employed for statistical analysis. Orthogonal contrasts were applied to evaluate main effects of DDGS, THR, and their interactions. In the results, Experiment 1 showed from 20 to 60 kg of BW 25% DDGS inclusion reduced (P < 0.01) FBW (63.4 vs 61.2 kg), ADG (0.88 vs 0.84 kg/d), and G:F (0.50 vs 0.49). There was an interaction between DDGS and THR on G:F (P < 0.01), where High THR improved G:F in diets containing 25% DDGS. In Experiment 2, reduced ADG (0.88 vs 0.81 kg/d) and G:F (0.53 vs 0.51) were observed for pigs fed 25% DDGS in grower phase (P < 0.01). In the early finisher, increased THR in diets with 25% DDGS improved (P < 0.01) FBW (90.54 vs 94.12 kg), ADG (0.95 vs 1.07 kg/d), and tended to improve G:F (P < 0.10; 0.37 vs 0.41), but not in pigs fed 0% DDGS. In summary, these two studies demonstrated greater SID Thr:Lys ratio may help offset the negative impact of fibrous diets on BW gain and feed efficiency in grow-finishing pigs.